A biosensor based on a film bulk acoustic resonator and biotin–avidin system for the detection of the epithelial tumor marker mucin 1. Issue 81 (3rd September 2015) - Guo, Peng; Xiong, Juan; Zheng, Dan; Zhang, Weihai; Liu, Lei; Wang, Shengfu; Gu, Haoshuang
<x xml:space="preserve">Abstract</x> A streptavidin-immobilized FBAR biosensor in virtue of specific binding between biotin and avidin was successfully fabricated for mucin 1 detection.